EFFECT OF TOBACCO EXTRACT ON STREPTOCOCCUS MUTANS: POSSIBLE ROLE IN MODULATING CARCINOGENESIS - Arun, Jyotsna; N, Srikant; Suman, Ethel; Shenoy, Ashok; Baliga, Srikala (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Tobacco use in the smoking or smokeless form is the most common form of substance abuse recorded in the world. Not only does tobacco influence carcinogenesis but also modifies the oral microflora. The aim of our study was to assess the growth pattern of Streptococcus mutans under the influence of cigarette extract. Methods: Pure stock culture of S. mutans was grown in brain heart infusion broth mixed with three concentrations of aqueous cigarette extract. Quantification of the S. mutans colonies was performed in Mitis Salivarius Agar subculture. Biofilm assessment was also performed to find the adherent property of microorganisms. Statistical Analysis used: One-way ANOVA was used to compare the effect of cigarette extract on growth and biofilm formation of S. mutans. Results: There was increase in the colony counts with increasing concentration of cigarette extract (p<0.001). There was an observable trend noted in the biofilm assay. Conclusion: The colony growth is positively influenced by the cigarette additives (sugars and sweeteners), carbon dioxide environment, and biofilm modification. The altered flora with higher S. mutans may be linked with the higher salivary acetaldehyde production which promotes carcinogenesis. The flora may be protective by production of antitumorigenic or antimutagenic compounds. The balance between the carcinogenic and anticarcinogenic signals produced by tobacco and microflora influences the outcome of the disease.